2005
DOI: 10.1093/jeg/lbi018
|View full text |Cite
|
Sign up to set email alerts
|

Geographically dispersed ownership and inter-market stock price arbitrage—Ahold's crisis of corporate governance and its implications for global standards

Abstract: Scandals of corporate governance in the United States and Europe in the aftermath of the TMT bubble captured the public imagination. In play were the interests of senior executives in relation to investors, prompting debate over countries' standards of corporate governance in the global market place. Ahold was (and is) an especially important instance, involving significant internal accounting and reporting failures and poor public disclosure of market-sensitive information. Ahold is also a global corporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…INEDs who have an interest at stake may behave differently from those who are fully independent because whilst they are deemed to be formally independent, in reality they may not be. Those INEDs may act in the interests of corporate insiders, collude with the CEO (or the controlling shareholder) and exercise their monitoring duties less efficiently (Melis, 2005;Clark, Wójcik & Bauer, 2006). …”
Section: H1: Ined's Remuneration Will Be Positively Related To the Inmentioning
confidence: 99%
“…INEDs who have an interest at stake may behave differently from those who are fully independent because whilst they are deemed to be formally independent, in reality they may not be. Those INEDs may act in the interests of corporate insiders, collude with the CEO (or the controlling shareholder) and exercise their monitoring duties less efficiently (Melis, 2005;Clark, Wójcik & Bauer, 2006). …”
Section: H1: Ined's Remuneration Will Be Positively Related To the Inmentioning
confidence: 99%
“…They document a negative relationship between European stock price volatility and ownership concentration, proving once again the importance of geography. In the same vein, the study of Clark, Wójcik, and Bauer (2006) [40] showed a negative relationship between the quality of corporate governance and stock price volatility. Clark and Wójcik (2007) [5] carried out a study on portfolio managers, the issue being whether they are better placed to pursue a passive-index strategy or an active-investment strategy in the specific case of the German industry.…”
Section: Geography Of Global Financementioning
confidence: 98%
“…Meanwhile the performance of Dutch food operator, Ahold has stagnated within the US, partly due to the shockwaves emanating from a 2003 financial scandal relating to significant accounting irregularities (Wrigley and Currah, 2003;Clark et al, 2006). While some of these problems stemmed from the retailer's Argentinian business (Wrigley and Currah, 2003), in the US, the retailer was forced to restate more than $800 million in earnings from its US Foodservice operation after executives had inflated promotional rebates from suppliers -something that led the retailer to pay $1.1 billion to the Securities and Exchange Commission (SEC) to resolve shareholder lawsuits (Tse and Williams, 2007).…”
Section: The Walmart Challenge: Scale Requirements the Spectre Of Chmentioning
confidence: 99%